Jerold E. Kemp Model Learning Design Based on Multimedia in Qur'an Hadith Lessons - Yelis Nur Wahidah; Muhammad Luthfi Assidiq; Muhammad Maliki (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2022)
The purpose of this research is to achieve an effective and efficient learning design in accordance with the planning and learning stages. The rapid evolution of the era of computer science will have an impact on all aspects, including aspects of education so that teachers are expected to be able to use multimedia technology in the learning process. This article also hopes that teachers can create effective and efficient learning projects using Jerold E. Kemp's learning model. The method used in writing this research is Classroom Action Research or Action Research, by applying the Jelord E. Kemp multimedia-based learning model to increase student interest in learning for class VII students and increase the diversity of learning models at MTs Assalam Peundeuy. The results show that the use of the Jerold E model Multimedia-based camps can increase the demands of learning in each cycle. seen from the pre-cycle data of 63.50% increased to 70.00% in the first cycle and increased to 82.00% in the second cycle.